THE RELATIONSHIP BETWEEN THE CONCEPTS OF SPACE AND TIME (Scientific journal of the Fergana State University, 2024)
Through studying and analyzing the relationship between the concepts of space and time in this article, it was found that they have been subjected to analysis and examination. It presents the opinions of several researchers on this matter. Philosophical about space and time summarizing the outlooking and the content of these categorizations, natural scientific knowledge of the world enriching with the basic properties of the space and time. Between space and time studying the sides of the relationship. Though, in this article explained studying the aspects of the difference and similarities between these concepts.